2012
DOI: 10.1007/s10040-011-0828-9
|View full text |Cite
|
Sign up to set email alerts
|

Hard-rock aquifers in tropical regions: using science to inform development and management policy

Abstract: An overview of progress during the past 30 years in the hydrogeologic understanding of groundwater in hard-rock aquifers of tropical regions is presented. Geographically, the paper concentrates upon and contrasts Tropical Africa and Peninsular India, where very extensive areas of weathered hard-rock aquifers occur, but its conclusions are more widely applicable. This scientific understanding forms the basis for a critical discussion of key policy issues for the development and management of the water resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 9 publications
0
19
0
3
Order By: Relevance
“…(Davis & De Wiest, 1996;Issar & Gilad, 1982;LeGrand, 1954;Summers, 1972). Calcaterra, Ietto, and Dattola (1993) Chilton & Foster, 1995;Foster, 2012;Maréchal et al, 2004;Taylor & Howard, 2000) have reported values of hydraulic transmissivity lower than 6 × 10 −4 m 2 s −1…”
Section: Palaeozoic Crystalline Hydrogeological Complexesmentioning
confidence: 99%
“…(Davis & De Wiest, 1996;Issar & Gilad, 1982;LeGrand, 1954;Summers, 1972). Calcaterra, Ietto, and Dattola (1993) Chilton & Foster, 1995;Foster, 2012;Maréchal et al, 2004;Taylor & Howard, 2000) have reported values of hydraulic transmissivity lower than 6 × 10 −4 m 2 s −1…”
Section: Palaeozoic Crystalline Hydrogeological Complexesmentioning
confidence: 99%
“…Recognition of this fissured layer as part of the weathering profile [16] and of its role in the basement aquifer drainage constitute a significant and recent advance for water resource management of basement rocks aquifers [5].…”
Section: The Weathering Profile Of Granitic Rocks and Its Relationshimentioning
confidence: 99%
“…Moreover, Ouagadougou is situated on basement rocks where aquifers are fully included in the few tens of meter thick weathering profile [3] [4] [5]. Therefore, the available groundwater resource is limited when compared to sedimentary aquifers [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…The fissures have been explained by several processes, such as lithostatic decompression, tectonic activity, cooling stress, and weathering processes. These two layers make up a composite aquifer followed in depth by the fresh basement, which is only locally permeable where tectonic fractures are present [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the bedrock transmissivity can vary over many orders of magnitude [3,7,[9][10][11][12][13]. Therefore, well yields are highly variable, and a high incidence of well failure occurs.…”
Section: Introductionmentioning
confidence: 99%